Pengaruh Return on Equity Terhadap Struktur Modal - Margita, Sekar Ayu (PRISMAKOM, 2026)
The purpose of this study is to determine the development of Return on Equity (ROE), Development of Capital Structure (DER), and the effect of Return on Equity (ROE) on Capital Structure at PT. BPR Sinar Mas Pelita for the period 2019-2024.The method used in this research is quantitative with a descriptive and associative approach. The data used is secondary data. Data collection techniques used in this study include documentation, observation, and literature review, with descriptive and statistical analysis.Based on the research results, it shows that Return on Equity (ROE) has a significant positive effect on Capital Structure. Testing conducted using simple linear regression analysis obtained a regression equation of Y = 233.828 + 2.531x. The correlation value of 0,825 is interpreted to have a very strong relationship. With a determination coefficient value of R square of 0.680 or 6.80% while the remaining 93.20% is influenced by other factors not examined. While the t test with the results of Thitung > Ttabel = (2.915 > 2.776) with a significant value of t of 0,043 <0,05. So it is expected that the company can be able to maximize the use of its own capital and borrowed capital so that the composition of the capital structure remains balanced and supports optimal financial performance.